Revisiting the Antigen-Presenting Function of β Cells in T1D Pathogenesis - Li, Yang; Sun, Fei; Yue, Tian-Tian; Wang, Fa-Xi; Yang, Chun-Liang; Luo, Jia-Hui; Rong, Shan-Jie; Xiong, Fei; Zhang, Shu; Wang, Cong-Yi (Frontiers in Immunology, 2021)
Type 1 diabetes (T1D) is characterized by the unresolved autoimmune inflammation and islet β cell destruction. The islet resident antigen-presenting cells (APCs) including dendritic cells and macrophages uptake and process the β cell-derived antigens to prime the autoreactive diabetogenic T cells. Upon activation, those autoreactive T cells pro-duce copious amount of IFN-γ, TNF-α and IL-1β to induce β cell stress and death. Autoimmune attack and β cell damage intertwine together to push forward this self-destructive program, leading to T1D onset. However, β cells are far beyond a passive participant during the course of T1D development. Herein in this review, we summarized how β cells are actively involved in the initiation of autoimmune responses in T1D setting. Specifically, β cells produce modified neoantigens under stressed con-dition, which is coupled with upregulated expression of MHC I/II and co-stimulatory molecules as well as other immune modules, that are essential properties normally ex-hibited by the professional APCs. At the cellular level, this subset of APC-like β cells dynamically interacts with plasmacytoid dendritic cells (pDCs) and manifests potency to activate autoreactive CD4 and CD8 T cells, by which β cells initiate early autoim-mune responses predisposing to T1D development. Overall, the antigen-presenting function of β cells helps to explain the tissue specificity of T1D and highlights the active roles of structural cells played in the pathogenesis of various immune related disorders.